Disparate biomechanical properties of the aorta in non‐aneurysmal and aneurysmal mice treated with angiotensin II. Issue 18 (18th September 2022) - De Moudt, Sofie; Hendrickx, Jhana O.; De Meyer, Guido R. Y.; Martinet, Wim; Fransen, Paul
Abstract: In vivo angiotensin II (AngII)‐treatment is a widely used experimental model to induce cardiovascular disease and results in a high likelihood of abdominal aorta aneurysm (AAA) formation. This involves progressive and irreversible focal dilation of the abdominal aorta and induces adverse aortic connective tissue remodeling contributing to aortic wall stiffening through inflammation, elastin degradation, and collagen restructuring. Hence, the present study aimed to investigate how AAA formation in AngII‐treated mice affects aortic function and biomechanics. To this end, C57Bl/6J mice were treated with AngII (1000 ng/[kg.min]) or PBS infusion for 28 days. Peripheral blood pressure, echocardiography, and aortic pulse wave velocity were measured in vivo. Thoracic aorta rings were studied ex vivo in organ chambers, while aortic vascular smooth muscle cell (VSMC) phenotype was investigated histologically. We confirmed peripheral hypertension, cardiac hypertrophy, aortic stiffening, and increased VSMC proliferation and migration after AngII‐treatment. Abdominal aorta aneurysm formation was observed in 8/13 AngII‐treated mice. Ex vivo thoracic aortic rings of both aneurysmal and non‐aneurysmal AngII‐treated mice showed high isobaric aortic stiffness, endothelial dysfunction, heightened α1 ‐adrenergic contractility, and altered VSMC contractile calcium signaling. However, aortic biomechanics were differently affected, with heightened α1 ‐adrenoreceptor mediated aortic stiffening in non‐aneurysmal mice, whereas contraction‐dependent stiffening was impaired in aneurysmal mice. In conclusion, although aneurysmal and non‐aneurysmal 4‐week AngII‐treated mice displayed similar changes in aortic physiology, aortic biomechanics were dissimilarly affected. Abstract : 4‐Week angiotensin‐II (AngII)‐treated C57Bl/6J mice displayed similar in vivo cardiovascular disease characteristics and isometric reactivity changes of the ex vivo thoracic aorta, independent of the development of abdominal aortic aneurysms. However, biomechanical properties of the aorta were dissimilarly affected between aneurysmal and non‐aneurysmal AngII‐treated mice, highlighting the importance of investigating vasoactive signaling pathways in the context of active modulation of aortic biomechanical behavior.